PERANG BAHASA DI MEDIA SOSIAL KASUS PENGANIAYAAN PADA ANAK SELEBGRAM EMY AGHNIA: KAJIAN SEMANTIK DAN PRAGMATIK - Aulia, Nanda Fitri; Ardhianti, Mimas (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Pattimura (Indonesia Language and Literature Education Department, The Faculty of Teacher's Training and Educational Sciences, University of Pattimura), 2024)
The purpose of this research is to find out (1) semantic studies and (2) pragmatic studies in the utterances of @emyaghnia's post upload comments. Researchers used a qualitative description type of research in this study. The upload of @emyaghnia's Instagram post is the source of data in this study. The data used in this study are in the form of screenshots of @emyaghnia's Instagram post upload comments. Data collection researchers use free listening techniques and record in this study as an instrument in this study, the data analysis technique used in this study is data reduction, data presentation and the last step is conclusion drawing. Based on the results of data analysis found by researchers, it can be concluded into two. First, the form of lexical and grammatical meaning in the comments of @emyaghnia's posts. The second data type of illocutionary speech acts found is expressive, and declarative. With this research, researchers can expand their understanding of semantics and pragmatics more deeply.